FORMULASI DAN UJI AKTIVITAS SEDIAAN GEL HANDSANITIZER MINYAK ATSIRI SEREH (Cymbopogon citratus) TERHADAP BAKTERI Pseudomonas aeruginosa - Andi Muhammad Farid; Djajanti, Agust Dwi Djajanti (Akademi Farmasi Yamasi Makassar, 2023)
Lemongrass (Cymbopogon citratus) is an essential oil-producing plant. The essential oil contained in lemongrass has properties, one of which is antiseptic. This study aims to make a formulation and test the physical stability and activity test of the Handsanitazer gel preparation of serch essential oil (Cymbopogon citratus) with three variations in concentration, namely 2%,3% and 4% with gel base The tests carried out on the three formulations included the physical properties of the gel, namely, organoleptic testing, pH, Homogeneity, dispersion, and Bacterial Activity. Antibacteria activity testing was carried out using the agar diffusion method which was modified using pure citronella essential oil (positive control), base gel (negative control) and gel preparations 2%,3%,4% Test data The bacterial activity obtained was analyzed by One Way Anova with 95% confidence level. The test results showed that the resulting gel met the test parameters, including the organoleptic test (semi solid, clear the typical smell of lemongrass), pH 5 which was still within a safe pH range of the skin, homogeneity with no visile coarse granules in all gel formulations, and strength test. Spread ranged from 6.2 to 7.6 Preparations of Gel Handsanitazer Lemongrass essential oil had anti-bacterial activity at a concentration of 2% with an Inhibition Zone of 22 mm. The results of the study showed the ability of Lemongrass Essential Oil to inhibit the growth of Pseudomonas aeruginosa.